Atlas of european values change and continuity in turbulent times - Halman, Loek; Reeskens, Tim; Sieben, Inge; van Zundert, Marga (European Values Series, 2022)
Do Europeans really feel European? Do they trust each other and are they solidary? What do they think of immigration and refugee influx? Do they want a greener and more sustainable Europe, and at what cost? Are democracy and human rights ingrained in Europe or are they under pressure? A new edition (2022) of the 'Atlas of European Values' answers these and other questions related to pressing topics such as migration, democracy, sustainability, welfare, identity, and solidarity in an attractive, visual way. In the Atlas, the reader will find maps, charts and graphs based on high-quality data of the long-term comparative survey research project, the European Values Study.